2011
DOI: 10.1103/physrevlett.106.236804
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Quantum Hall States at Zero Magnetic Field

Abstract: We present a simple prescription to flatten isolated Bloch bands with a nonzero Chern number. We first show that approximate flattening of bands with a nonzero Chern number is possible by tuning ratios of nearest-neighbor and next-nearest-neighbor hoppings in the Haldane model and, similarly, in the chiral-π-flux square lattice model. Then we show that perfect flattening can be attained with further range hoppings that decrease exponentially with distance. Finally, we add interactions to the model and present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
979
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 906 publications
(1,029 citation statements)
references
References 23 publications
20
979
1
Order By: Relevance
“…More interesting physics occurs when the nearly flat 'Chern' band is partially filled (see Figs 2e and 4). In this case, as pointed out recently, fractional quantum Hall (FQH) states are likely to be realized [39][40][41][42][43][44] . To elaborate this possibility, we perform exact diagonalization calculation after projecting on-site repulsion and NN repulsion into the 1/3 filled highest Chern band (that is, at e g 3.5 + 1/6 ).…”
Section: Resultsmentioning
confidence: 78%
“…More interesting physics occurs when the nearly flat 'Chern' band is partially filled (see Figs 2e and 4). In this case, as pointed out recently, fractional quantum Hall (FQH) states are likely to be realized [39][40][41][42][43][44] . To elaborate this possibility, we perform exact diagonalization calculation after projecting on-site repulsion and NN repulsion into the 1/3 filled highest Chern band (that is, at e g 3.5 + 1/6 ).…”
Section: Resultsmentioning
confidence: 78%
“…The proposed topological FB is just like a counterpart of the LL, characterized by a Chern number equal to 1 [12]. It has been further shown by numerical simulations that such FBs support QH-like states, exhibiting not only the integer QH effects, but also the fractional QH (FQH) effects [20][21][22]. More importantly, considering the energy scales in lattices, the FQH effects -such as fractionalization and entanglement -can be realized in a much higher temperature in the FB than in the LL [18], charting a revolutionary route towards quantum computation [23].…”
Section: Introduction and Scopementioning
confidence: 81%
“…They are characterized by different PSGs in the bulk. These states can all serve as candidate states for the FCI state found in numerical simulations 12,13,15 . Which state is realized in the simulated model 12,13,15 would be determined by energetics.…”
Section: Introductionmentioning
confidence: 99%
“…However, it takes more than two decades for people to show that similar statement is true even for FQHE. Recently results from a series of model studies [10][11][12][13][14][15][16][17][18] , including convincing evidences from exact diagonalizations [12][13][14][15][16][17] , indicate that fractional quantum hall states exist in the ground states of interacting lattice models, in the absence of an external magnetic field. It is found that the ground state is likely to respect the full lattice symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation